Prevention and early intervention with children in need - Little, Michael; Mount, Kevin (Routledge revivals., 2018)
First published in 1999, this volumeexamines how, inthe middle of the nineteenth century, Dr John Snow is reputed to have wrenched the handle from a street pump in central London, forcing people in the neighbourhood to change their drinking habits and so preventing them from contracting cholera from the dirty water. Aspects of the story may be apocryphal, but the general drift of Snow's assault on disease has enormous appeal for health, education, social services and police professionals working with children in need. Why spend so much time struggling to find strategies to cope with the more intractable problems among adolescents, when the problems might be prevented from occurring in the first place? This book tries to untangle some of the complex ideas that underpin effective prevention and early intervention activity on behalf of children experiencing social or psychological difficulty. It describes twenty programmes from Europe and America that have made an impact and where there has been an attempt to evaluate their usefulness. On this basis it suggests some principles for more effective preventive practice.